Decayed, Missing, and Filled Teeth Index and Periodontal Health in Osteoporotic Patients Affected by BRONJ: An Observational Study - Giacomo Oteri; Ennio Bramanti; Valentina Nigrone; Marco Cicciù (Journal of Osteoporosis)
The aim of this paper is to describe the incidence of decayed, missing, and filled teeth (DMFT) and periodontal disease in 32 osteoporotic patients affected by bisphosphonate-related osteonecrosis of the jaw (BRONJ). Moreover, an investigation between the obtained data and 20 patients treated with bisphosphonate drugs and with no evidence of ONJ has been performed. Osteonecrosis of the jaws is a rare complication in a subset of patients receiving bisphosphonate drugs. Based on a growing number of case reports and institutional reviews, this kind of therapy can cause exposed and necrotic bone specifically in the jawbones. From April 2009 to June 2012, 32 osteoporotic patients treated with oral or intravenous (I.V.) bisphosphonates have been recorded. The patients’ oral health has been compared with 20 bisphosphonates patients with no ONJ. The incidence of decayed, missing, and filled teeth (DMFT) and periodontal disease was recorded in all patients and student’s t-test was applied for comparing the two investigated groups data. Data demonstrated how the poor dental hygiene and periodontal disease of the BRONJ patients’ are connected with the occurrence of jawbone necrosis.